VIBRATION NONLINEAR ANALYSIS OF DIESEL VALVE GEAR - Jurij Avsec; Andrej Predin (Journal of Energy Technology, 2024)
This paper describes the nonlinear vibration analysis of a new type of valve gear. In order to estimate the cam wear intensity and to compare the new cam designs with the existing ones the dynamic vibration valve gear analysis was made. The real model of the real valve gear design can be written by means of the partial differential equations, the solution of which is a complex task. We used a vibration system with three degrees of freedom. The differential equations were solved by finite differences method and RungeͲKutta method. With help of our models we are able to analyze the kinematics and dynamic behaviour of nonlinear valve spring. On the basis of presented theory we will find in the future research the conditions for chaotic behaviour of valve gear system.